Thermal and non-thermal processing of kelulut honey: effect on physicochemical properties, brown pigment and antioxidant activity - Mohd Fauzi, Noor Akhmazillah; Md.Amir Hamzah, Halimatu el Sa’diah; Mislam, Nurhanisah; A Rahman, Nur Atikah binti (Penerbit UTHM, 2017)
Honey of Trigona sp. or known as Kelulut honey is a natural product unique to Malaysia that has been reported as having higher nutritional values. However, the application of conventional thermal treatment for commercial honey processing plant can be detrimental to physicochemical properties and antioxidant activity due to the unstable and thermolabile components when heated at 60 and above. Therefore, the objective of this study was to investigate the application of non-thermal processing (indirect ultrasound and double boiling) as an alternative to the thermal treatment in order to minimize the effect of heat on the quality of Kelulut honey. The present study was undertaken to assess the effect of both treatments on the physicochemical properties (pH, moisture content, total soluble solid and total solid) and nutritional properties (brown pigment and antioxidant activity) of Kelulut honey. In the long run, this research aims to propose an alternative honey processing which can guarantee the enhancement Kelulut honey as a natural resources food.